Bovine blood derived macrophages are unable to control Coxiella burnetii replication under hypoxic conditions - Mauermeir, Michael; Ölke, Martha; Hayek, Inaya; Schulze-Lührmann, Jan; Dettmer, Katja; Oefner, Peter J.; Berens, Christian; Menge, Christian; Lührmann, Anja (Frontiers in Immunology, 2023)
Background: Coxiella burnetii is a zoonotic pathogen, infecting humans, livestock, pets, birds and ticks. Domestic ruminants such as cattle, sheep, and goats are the main reservoir and major cause of human infection. Infected ruminants are usually asymptomatic, while in humans infection can cause significant disease. Human and bovine macrophages differ in their permissiveness for C. burnetii strains from different host species and of various genotypes and their subsequent host cell response, but the underlying mechanism(s) at the cellular level are unknown. Methods: C. burnetii infected primary human and bovine macrophages under normoxic and hypoxic conditions were analyzed for (i) bacterial replication by CFU counts and immunofluorescence; (ii) immune regulators by westernblot and qRT-PCR; cytokines by ELISA; and metabolites by gas chromatography-mass spectrometry (GC-MS). Results: Here, we confirmed that peripheral blood-derived human macrophages prevent C. burnetii replication under oxygen-limiting conditions. In contrast, oxygen content had no influence on C. burnetii replication in bovine peripheral blood-derived macrophages. In hypoxic infected bovine macrophages, STAT3 is activated, even though HIF1α is stabilized, which otherwise prevents STAT3 activation in human macrophages. In addition, the TNFα mRNA level is higher in hypoxic than normoxic human macrophages, which correlates with increased secretion of TNFα and control of C. burnetii replication. In contrast, oxygen limitation does not impact TNFα mRNA levels in C. burnetii-infected bovine macrophages and secretion of TNFα is blocked. As TNFα is also involved in the control of C. burnetii replication in bovine macrophages, this cytokine is important for cell autonomous control and its absence is partially responsible for the ability of C. burnetii to replicate in hypoxic bovine macrophages. Further unveiling the molecular basis of macrophage-mediated control of C. burnetii replication might be the first step towards the development of host directed intervention measures to mitigate the health burden of this zoonotic agent.
CRIS-Team Scopus Importer:2023-02-24
Keywords: bovine macrophages; citrate; Coxiella burnetii; HIF1α; hypoxia; normoxia; STAT3; TNF

Cell death induction facilitates egress of Coxiella burnetii from infected host cells at late stages of infection - Schulze-Lührmann, Jan; Liebler-Tenorio, Elisabeth; Felipe-López, Alfonso; Lührmann, Anja (Molecular Microbiology, 2023)
Intracellular bacteria have evolved mechanisms to invade host cells, establish an intracellular niche that allows survival and replication, produce progeny, and exit the host cell after completion of the replication cycle to infect new target cells. Bacteria exit their host cell by (i) initiation of apoptosis, (ii) lytic cell death, and (iii) exocytosis. While bacterial egress is essential for bacterial spreading and, thus, pathogenesis, we currently lack information about egress mechanisms for the obligate intracellular pathogen C. burnetii, the causative agent of the zoonosis Q fever. Here, we demonstrate that C. burnetii inhibits host cell apoptosis early during infection, but induces and/or increases apoptosis at later stages of infection. Only at later stages of infection did we observe C. burnetii egress, which depends on previously established large bacteria-filled vacuoles and a functional intrinsic apoptotic cascade. The released bacteria are not enclosed by a host cell membrane and can infect and replicate in new target cells. In summary, our data argue that C. burnetii egress in a non-synchronous way at late stages of infection. Apoptosis-induction is important for C. burnetii egress, but other pathways most likely contribute.
CRIS-Team Scopus Importer:2023-12-29
Keywords: apoptosis; Coxiella burnetii; egress; Q fever; spreading

Interdisciplinary studies on Coxiella burnetii: From molecular to cellular, to host, to one health research - Bauer, Benjamin U.; Knittler, Michael R.; Andrack, Jennifer; Berens, Christian; Campe, Amely; Christiansen, Bahne; Fasemore, Akinyemi M.; Fischer, Silke F.; Ganter, Martin; Körner, Sophia; Makert, Gustavo R.; Matthiesen, Svea; et al. (International Journal of Medical Microbiology, 2023)
The Q-GAPS (Q fever GermAn interdisciplinary Program for reSearch) consortium was launched in 2017 as a German consortium of more than 20 scientists with exceptional expertise, competence, and substantial knowledge in the field of the Q fever pathogen Coxiella (C.) burnetii. C. burnetii exemplifies as a zoonotic pathogen the challenges of zoonotic disease control and prophylaxis in human, animal, and environmental settings in a One Health approach. An interdisciplinary approach to studying the pathogen is essential to address unresolved questions about the epidemiology, immunology, pathogenesis, surveillance, and control of C. burnetii. In more than five years, Q-GAPS has provided new insights into pathogenicity and interaction with host defense mechanisms. The consortium has also investigated vaccine efficacy and application in animal reservoirs and identified expanded phenotypic and genotypic characteristics of C. burnetii and their epidemiological significance. In addition, conceptual principles for controlling, surveilling, and preventing zoonotic Q fever infections were developed and prepared for specific target groups. All findings have been continuously integrated into a Web-based, interactive, freely accessible knowledge and information platform (www.q-gaps.de), which also contains Q fever guidelines to support public health institutions in controlling and preventing Q fever. In this review, we will summarize our results and show an example of how an interdisciplinary consortium provides knowledge and better tools to control a zoonotic pathogen at the national level.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Immune subversion/defense; Molecular epidemiology; One Health; Q fever; Ruminants; Virulence factors; Zoonosis

Itaconate mediates control of Coxiella burnetii infection in murine macrophages - Siddique, Md Nur A Alam; Kohl, Lisa; Berger, Raffaela; Schulze-Lührmann, Jan; Lührmann, Anja; Wilde, Katja Dettmer; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate

The Coxiella burnetii T4SS effector protein AnkG hijacks the 7SK small nuclear ribonucleoprotein complex for reprogramming host cell transcription - Cordsmeier, Arne; Rinkel, Sven; Jeninga, Myriam; Schulze-Lührmann, Jan; Oelke, Martha; Schmid, Benedikt; Hasler, Daniele; Meister, Gunter; Haecker, Georg; Petter, Michaela; Beare, Paul A.; Lührmann, Anja (PLoS Pathogens, 2022)
Inhibition of host cell apoptosis is crucial for survival and replication of several intracellular bacterial pathogens. To interfere with apoptotic pathways, some pathogens use specialized secretion systems to inject bacterial effector proteins into the host cell cytosol. One of these pathogens is the obligate intracellular bacterium Coxiella burnetii, the etiological agent of the zoonotic disease Q fever. In this study, we analyzed the molecular activity of the anti-apoptotic T4SS effector protein AnkG (CBU0781) to understand how C. burnetii manipulates host cell viability. We demonstrate by co- and RNA-immunoprecipitation that AnkG binds to the host cell DExD box RNA helicase 21 (DDX21) as well as to the host cell 7SK small nuclear ribonucleoprotein (7SK snRNP) complex, an important regulator of the positive transcription elongation factor b (P-TEFb). The co-immunoprecipitation of AnkG with DDX21 is probably mediated by salt bridges and is independent of AnkG-7SK snRNP binding, and vice versa. It is known that DDX21 facilitates the release of P-TEFb from the 7SK snRNP complex. Consistent with the documented function of released P-TEFb in RNA Pol II pause release, RNA sequencing experiments confirmed AnkG-mediated transcriptional reprogramming and showed that expression of genes involved in apoptosis, trafficking, and transcription are influenced by AnkG. Importantly, DDX21 and P-TEFb are both essential for AnkG-mediated inhibition of host cell apoptosis, emphasizing the significance of the interaction of AnkG with both, the DDX21 protein and the 7SK RNA. In line with a critical function of AnkG in pathogenesis, the AnkG deletion C. burnetii strain was severely affected in its ability to inhibit host cell apoptosis and to generate a replicative C. burnetii-containing vacuole. In conclusion, the interference with the activity of regulatory host cell RNAs mediated by a bacterial effector protein represent a novel mechanism through which C. burnetii modulates host cell transcription, thereby enhancing permissiveness to bacterial infection.
CRIS-Team Scopus Importer:2022-02-25